2017
DOI: 10.1186/s12882-017-0576-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor activation reduces inflammatory cytokines and plasma MicroRNAs in moderate chronic kidney disease – a randomized trial

Abstract: BackgroundChronic kidney disease (CKD) is a major risk factor for cardiovascular disease (CVD), partly due to endothelial dysfunction and chronic inflammation. Vitamin D treatment in end stage renal disease is suggested to modulate the immune system and lead to improved outcomes. We and others have demonstrated that treatment with vitamin D or activated vitamin D analogues protects the endothelial function in less severe renal disease as well. Since the endothelial protection might be mediated by vitamin D eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The protective effect of vitamin D/VDR in kidney diseases has been validated by a lot of research works including ours 10,21 . While most of those work mainly focused on chronic kidney diseases like diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The protective effect of vitamin D/VDR in kidney diseases has been validated by a lot of research works including ours 10,21 . While most of those work mainly focused on chronic kidney diseases like diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies including our previous work have shown that 1,25(OH)2D3 or its active analogs, through VDR activation, are protective against proteinuria, renal fibrosis, and inflammation in patients with chronic kidney disease and in animal models of diabetic nephropathy or end-stage renal disease [10][11][12][13] . However, few attentions were focused on the role of VDR in AKI.…”
Section: Introductionmentioning
confidence: 98%
“…Vitamin D supplementation has been proven to modulate some of the miRNAs posing a risk towards MS, such as miR-146a, miR-150, miR-155, miR-30c, miR-23a, miR-181b, miR-449c, miR-125b, miR-7, and miR-432-5p. 120,[182][183][184][185][186] It was also linked to EAE amelioration. 120 The EBV drug, ACV, was related to a significant downregulation of MS-associated miR-146a.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, miR-7 was observed to be increased in EAE lymph nodes (P = 1.2E-03, fold change = 1.4) ( Table 2). 153 In an article by Mansouri et al, 186 daily supplementation of 2 μg paricalcitol in 12 patients with chronic kidney disease (CKD) significantly reduced the levels of miR-432-5p, miR-495-3p, and miR-576-5p compared with those in the placebo group (n = 12). miR-432-5p was reported to be a significantly dysregulated miRNA that could distinguish between healthy controls and progressive MS and between progressive MS and RRMS (P = .002, 0.051, fold-change = 2.2, 0.5; respectively).…”
Section: Table 5 (Continued)mentioning
confidence: 99%
“…Activation of the transcription nuclear factor-κB (NF-κB) and the intrarenal renin-angiotensin system, in ltration of macrophages, and tubulointerstitial in ammation may also be involved [10,35]. On the contrary, vitamin D has been shown to reduce levels of reactive oxygen species, suppress renin-angiotensin system and decrease circulating angiotensin II levels, inhibit in ammatory responses, and prevent podocyte loss and glomerulosclerosis [13,36,37], thereby potentially protect kidney from damage induced by lead exposure. A recent study in rats revealed that vitamin D alleviated lead induced kidney injury (i.e.…”
Section: Discussionmentioning
confidence: 99%